Minimal acute toxicity from proton beam therapy for major salivary gland cancer. (1st February 2020) - Chuong, Michael; Bryant, John; Hartsell, William; Larson, Gary; Badiyan, Shahed; Laramore, George E.; Katz, Sanford; Tsai, Henry; Vargas, Carlos
Abstract: Introduction: Proton beam therapy (PBT) reduces normal organ dose compared to intensity-modulated radiation therapy (IMRT) for patients with major salivary gland tumors. It is not known whether this dosimetric advantage is clinically meaningful for reducing acute toxicity. Methods: We evaluated treatment parameters and acute toxicity outcomes of patients with major salivary gland cancers enrolled on the Proton Collaborative Group REG001-09 trial (NCT01255748). Results: One-hundred and five patients with a median age of 61 years were included. The majority had parotid ( N = 90) versus submandibular gland ( N = 15) tumors. The patients were treated across seven institutions in the United States between 2010 and 2017, most commonly in the postoperative setting (70.5%) although a minority were treated definitively (29.5%). Median PBT dose was 66.5 GyE in 33 fractions; only one patient was prescribed less than 50 GyE. Chemotherapy was given concurrently to 20%. Median follow-up was 14.3 months. Acute grade 2 or higher toxicity included nausea (1.5%), dysgeusia (4.8%), xerostomia (7.6%), mucositis (10.5%) and dysphagia (10.5%). Conclusions: PBT should be strongly considered when ipsilateral radiation therapy is indicated for major salivary gland cancer based on a considerably lower incidence of acute grade 2 or higher toxicity in this analysis compared to historical IMRT outcomes.